2008
DOI: 10.1128/cvi.00258-07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Oral Disease on Systemic Inflammatory and Immune Parameters in Nonhuman Primates

Abstract: This report evaluated systemic inflammatory and immune biomarkers in a cohort of Macaca mulatta (rhesus monkeys) maintained as a large family social unit, including an age range from <1 year to >24 years. We hypothesized that the systemic host responses would be affected by the age, gender, and clinical oral presentation of the population, each contributing to inflammatory and immune responses that would reflect chronic oral infections. The results demonstrated that the prevalence and severity of periodontitis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
87
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(91 citation statements)
references
References 83 publications
2
87
1
Order By: Relevance
“…The clinical examination included probing pocket depth (PD) and bleeding on probing (BOP; 0-3 scale) (Ebersole et al, 2008). Clinical characterization for each group Genes shown in red are over-expressed, and genes shown in yellow are under-expressed in young gingival tissue compared with aged gingival tissue.…”
Section: Oral Clinical Parameters and Gingival Tissue Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical examination included probing pocket depth (PD) and bleeding on probing (BOP; 0-3 scale) (Ebersole et al, 2008). Clinical characterization for each group Genes shown in red are over-expressed, and genes shown in yellow are under-expressed in young gingival tissue compared with aged gingival tissue.…”
Section: Oral Clinical Parameters and Gingival Tissue Sample Collectionmentioning
confidence: 99%
“…Consistent with age being a modifier for the prevalence or severity of periodontal disease, important biological differences in the composition and complexity of the oral microbial ecology, as well as the oral/systemic immune-inflammatory responses during aging, have been described in humans and animal models (Schlegel-Bregenzer et al, 1998;Nonnenmacher et al, 2001;Ebersole et al, 2008). Paradoxically, the reduced immunity in aging is accompanied by chronic inflammation (Back et al, 2007), which may reflect a perturbation of the innate immune mechanisms associated with age (Agrawal et al, 2007).…”
mentioning
confidence: 96%
“…Biological changes in response to this chronic polymicrobial infection can be measured in the local periodontal environment, as well as systemically (26,38,39). Evidence from oral infections related to dental caries has demonstrated that young humans are infected early in life with Streptococcus mutans, generally contracted from the primary caregiver (40,41).…”
mentioning
confidence: 99%
“…Signature species differences in the composition of the bacterial population at specific niches have been demonstrated and shown to correlate with infections including caries, endodontic infections, gingivitis, subgingival plaque and periodontitis (Siqueira and Rocas 2004;Zijnge et al 2010). The composition of the oral bacterial community varies significantly among individuals and changes with age, diet, hygiene, anatomical niche, health status, and other factors (Darveau 2010;Ebersole et al 2008). As periodontal disease progresses, significant changes occur in the physiochemical and immunological environment of the gingival sulcus or subgingival crevice (the space between the tooth and gum tissue) (reviewed in McDowell et al 2012).…”
Section: Introductionmentioning
confidence: 99%